2019
DOI: 10.5863/1551-6776-24.6.489
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitors, H2 Blocker Use, and Risk of Inflammatory Bowel Disease in Children

Abstract: OBJECTIVES Evidence suggests use of proton pump inhibitors (PPIs) and H2 blockers may provoke disease flares in individuals with established inflammatory bowel disease (IBD); however, there are no studies investigating the relationship of these medications with risk of developing pediatric IBD. The hypothesis was that use of acid suppression therapy in children might be associated with development of pediatric IBD. METHODS This was a nested case-control study of 285 Kaiser Permanente Northern California membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
32
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 35 publications
3
32
0
2
Order By: Relevance
“…Out results were in line with a recent nested case-control study of 286 patients with pediatric IBD and 1144 controls, which showed that PPI was significantly associated with increased risk (odds ratio, 3.6; 95% CI, 1.1-11.7), and no sufficient evidence of increased risk was observed for H2RAs (odds ratio, 1.6; 95% CI, 0.7-3.7). 16 In patients with established IBD, many studies have reported that PPIs might increase the severity of the disease and lead to treatment escalation. [21][22][23] For example, a meta-analysis of 5 randomized trials found that patients with IBD taking PPIs were less likely to achieve remission while on infliximab therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Out results were in line with a recent nested case-control study of 286 patients with pediatric IBD and 1144 controls, which showed that PPI was significantly associated with increased risk (odds ratio, 3.6; 95% CI, 1.1-11.7), and no sufficient evidence of increased risk was observed for H2RAs (odds ratio, 1.6; 95% CI, 0.7-3.7). 16 In patients with established IBD, many studies have reported that PPIs might increase the severity of the disease and lead to treatment escalation. [21][22][23] For example, a meta-analysis of 5 randomized trials found that patients with IBD taking PPIs were less likely to achieve remission while on infliximab therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent nested case-control study found that PPI was significantly associated with increased risk of pediatric IBD. 16 A large randomized controlled trial 8 and meta-analyses of observational studies [17][18][19] have demonstrated that PPI use could facilitate gastrointestinal infections, such as C difficile infection, which are known to associate with development of IBD. 5,20 In patients with IBD, PPIs may provoke disease flares, 21,22 and were associated with lower remission rate.…”
mentioning
confidence: 99%
“…The increased use of PPI medication in children has raised concerns among paediatric gastroenterologists. 10 Long-term PPI use has been associated with potentially harmful alteration of the gut microbiome, 21 increased risk of inflammatory bowel disease 22 and bacterial infections in the GI tract. 5 Therefore, it is essential to restrain the medication for patients with objective proof of excessive acidic GOR.…”
Section: Discussionmentioning
confidence: 99%
“…У базових схемах лікування кислотнозалежних хвороб ШКК переважають БПП завдяки більш високій кислотоблокувальній здатності [9]. Однак БПП мають низку недоліків, серед яких великий відсоток пацієнтів, резистентних до тих чи інших БПП, а також можливість так званого нічного кислотного прориву [5,24]. Крім цього, застосовуючи БПП лікар-інтерніст мусить оцінювати не тільки кислотнознижувальний ефект ЛЗ, а й інші впливи на орґанізм [9].…”
unclassified
“…Вільну й загальну кислотність шлункового соку визначали титраційним методом [7], а також проводили титрування шлункового соку з використанням рН-метра для оцінки активності іонів водню [14]. Уміст пепсиноґену визначали колориметричним методом [11,26], сіалових кислот (N-acetylneuraminicacid-NANA), як маркера мукоїдної секреції -резорциновим методом у шлунковому соці та нерозчинному слизі [13,24]. Концентрацію натрію, як маркера гідрокарбонатної секреції, в шлунковому соці та нерозчинному слизі визначали полуменево-фотометричним методом [14].…”
unclassified